THE IMPACT OF PHYSICAL EXERCISES ON CHANGES IN THE FUNCTIONAL STATE OF THE HUMAN BODY AND POSTURE - Maskayeva, Tatyana; Shmeleva, Svetlana; Zolotova1, Maria; Vakulenko, Antonina; Logachev, Nikita; Vorobeva, Nadezhda (Revista Inclusiones, 2020)
Physical exercises are still considered a powerful stimulant of all physiological processes in the human body. As a result, dosed physical activity is a targeted stimulant for all life processes in the body. This effect of regular exercises is related to their optimising effect on all body systems and organs. Using various types of physical activity, it is possible to regulate morpho-functional parameters of the body to optimise its physical condition. This is entirely true in terms of the effect on posture. This parameter is very important because it reflects the features of the vertical position of the spine in the development of adaptive reactions in the body, ensuring that the body maintains its vertical posture. Redistribution of physical activity on different parts of the spine under the influence of exercise corrects posture through selective training of body muscles and straightening of the spine. Optimising the tone of the back muscles leads to visible positive changes in the configuration of the spine, ultimately optimising posture. Physical exercises of people with postural disorders should always be aimed at preventing their progress and correcting existing spinal curves. This is best achieved in weight-bearing exercises.